2010
DOI: 10.1248/jhs.56.613
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Bovine Lactoferrin on Human Parainfluenza Virus Type 2 Infection

Abstract: Lactoferrin (Lf) is a multifunctional protein that has inhibitory activity against microorganisms. In this study, the effects of Lf on the growth of human parainfluenza virus type 2 (hPIV-2) in LLCMK 2 cells were investigated. Lf inhibited cell fusion and hemadsorption induced by hPIV-2. However, virus RNA synthesis was only slightly inhibited by Lf. In addition, indirect immunofluorescence study showed that virus protein syntheses were not completely inhibited by Lf. Using a recombinant, green fluorescence pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Successively, Sanoand co-workers [ 109 ] showed that RSV-induced IL-8 secretion from HEp-2 cells was down regulated by lactoferrin and that both RSV infectivity and uptake were decreased by lactoferrin treatment. Toclarify the mechanism of this effect, the interaction of lactoferrin with RSV F protein, the mostimportant surface glycoprotein for viral penetration, was examined and results obtained showed thatlactoferrin directly interacted with the F (1) subunit, which involved antigenic sites of F protein [ 109 ].Concerning PIV, Lf exhibits antiviral activity against hPIV-2 by inhibiting virus adsorption to the surface of the cells thus preventing viral infection and replication [ 110 ].…”
Section: Inhibition Of Viral Infections By Lactoferrinmentioning
confidence: 99%
“…Successively, Sanoand co-workers [ 109 ] showed that RSV-induced IL-8 secretion from HEp-2 cells was down regulated by lactoferrin and that both RSV infectivity and uptake were decreased by lactoferrin treatment. Toclarify the mechanism of this effect, the interaction of lactoferrin with RSV F protein, the mostimportant surface glycoprotein for viral penetration, was examined and results obtained showed thatlactoferrin directly interacted with the F (1) subunit, which involved antigenic sites of F protein [ 109 ].Concerning PIV, Lf exhibits antiviral activity against hPIV-2 by inhibiting virus adsorption to the surface of the cells thus preventing viral infection and replication [ 110 ].…”
Section: Inhibition Of Viral Infections By Lactoferrinmentioning
confidence: 99%
“…Here, we report that ASL from the airways of pigs and humans exhibits Several mechanisms are responsible for the antiviral actions of these proteins and peptides, including direct binding to and aggregation of viruses through interactions with lipid bilayers and/or viral glycoproteins, and in some cases disruption of viral membranes (40,41). In contrast, lactoferrin inhibits parainfluenza virus 2 (PIV2) infection by binding to cellular proteins rather than through direct interaction with the virus (43). Additionally, airway mucins are thought to contribute to antiviral defenses by interacting with viruses in ways that impede their movement and/or prevent their uptake (48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…In Madin-Darby canine kidney cells, human LF (20-80 µg/mL) demonstrated enhanced antiviral activity against avian IAV in a dose-dependent manner [85]. In addition, bovine LF inhibited parainfluenza virus replication in vitro and decreased viral adsorption onto cells, thereby preventing viral entry [86]. Together these results highlight the possible role of LF in preventing influenza and parainfluenza virus infections.…”
Section: Transferrinsmentioning
confidence: 99%